The mediating role of emotion regulation on the effect of parental pressure for greater academic performance on gaming addiction - EKŞİ, HALİL; YAMAN, KAMİLE GAMZE (My University, 2022)
Today, the use of technology and the interest in technology-based games are very important for school-age children. This study seeks to use a Structural Equation Model (SEM) to examine the mediating role of difficulties in emotion regulation in the relationship between parental pressure for greater academic performance and gaming addiction in high school students. Additionally, this study endeavors to investigate gaming addiction, difficulties in regulating emotions, and parental pressure for greater academic performance through diverse variables. Using multistage cluster sampling to select participants from the universe, the study sample consists of 627 high school students aged 14- 17 studying in various districts within the province of Istanbul, Turkey. The data for this study were collected using the Personal Information Form, the Gaming Addiction Scale for Adolescents, the Difficulties in Emotion Regulation Scale, and the Parental Pressure and Support for Greater Academic Performance Scale. An Independent Samples t-Test, an ANOVA, Pearson’s Product-Moment Correlation, and a Path Analysis were used to analyze the study’s data. After analysis of the SEM constructed for this study, we found that parental pressure for greater academic performance had a very high, direct effect on gaming addiction, that this effect decreased after including difficulties in emotion regulation as a mediating variable, and that parental pressure for greater academic performance had a low, indirect effect on gaming addiction through difficulties in emotion regulation. The results of the SEM analyses show that the fit indices of the model in question were within acceptable limits and that the model accounted for 21% of the total variance of gaming addiction

Günümüzde teknoloji kullanımı ve teknoloji temellli oyunlara yönelik ilgi okul çağı çocukları için oldukça önem arz etmektedir. Bu çalışmanın amacı lise öğrencilerinin ebeveynlerinin çocuklarına yönelik akademik başarı baskısının oyun bağımlılığı üzerindeki etkisinde duygu düzenleme güçlüğünün aracı rolünü Yapısal Eşitlik Modeli çerçevesinde incelemek ve oyun bağımlılığın, duygu düzenleme güçlüğünün, ebeveyn akademik başarı baskısının çeşitli değişkenlerle ilişkisini araştırmaktır. Araştırmanın örneklemini, İstanbul ilinde öğrenim gören lise öğrencilerini kapsamına alan araştırma evreninden çok aşamalı küme örnekleme yöntemi ile seçilen 14-17 yaş arası 627 öğrenci oluşturmaktadır. Araştırma verileri; Kişisel Bilgi Formu, Ergenler İçin Oyun Bağımlılığı Ölçeği, Duygu Düzenleme Güçlüğü Ölçeği ve Ebeveyn Akademik Başarı Baskısı ve Desteği Ölçeği ile toplanmıştır. Araştırmanın amaçları doğrultusunda yapılan veri analizlerinde Bağımsız Gruplar t-Testi, ANOVA (Tek Yönlü Varyans Analizi), Pearson Momentler Çarpımı Korelasyonu ve Yol Analizi kullanılmıştır. Çalışmanın amacı uyarınca kurulan Yapısal Eşitlik Modeli’ne göre ebeveyn akademik başarı baskısının oyun bağımlılığına doğrudan etkisinin oldukça yüksek olduğu, duygu düzenleme güçlüğünün aracı değişken olarak modele dâhil edilmesiyle ebeveyn akademik başarı baskısının oyun bağımlılığı üzerindeki etkisinin azaldığı, ebeveyn akademik başarı baskısının duygu düzenleme güçlüğü üzerinden oyun bağımlılığına dolaylı etkisinin düşük düzeyli olarak gerçekleştiği görülmektedir. YEM analizi sonuçları bakımından, test edilen modelin uyum indekslerinin kabul edilebilir düzeyde olduğu bulgulanmıştır. Kurulan model üzerinden oyun bağımlılığı değişkeninin toplam varyansının %21’lik bir kısmının açıklandığı görülmüştür.
Keywords: Addiction; Parental Pressure for Greater Academic; Performance; Difficulties in Emotion Regulation; Oyun Bağımlılığ; ı Ebeveyn Akademik Başarı Baskısı; Duygu Düzenleme Güçlüğü